The Effect of Varying Oat Beverage Ratios on the Characteristics of Fermented Dairy–Oat Beverages - Małgorzata Ziarno; Dorota Zaręba; Ewa Kowalska; Tomasz Florowski (Applied Sciences)
In the context of the growing popularity of plant–based diets and the search for alternatives to traditional dairy products, there is a need to develop new, consumer–appealing products that combine the nutritional value of milk and oats. The aim of this study was to investigate the effects of different proportions of oat beverage in cow’s milk on the physicochemical, textural, sensory, and microbiological properties of fermented dairy–oat beverages, as well as to assess the stability of these properties during cold storage. Dairy–oat beverages with varying percentages of oat beverage (0–100%) were prepared and subjected to fermentation using starter cultures of S. thermophilus and L. delbrueckii subsp. bulgaricus. Changes in pH, lactose content, color, syneresis, texture, and starter bacteria population were evaluated over 28 days of storage at 6 °C. The results showed that the addition of oat beverage significantly affected the chemical composition, fermentation process, and quality characteristics of the final product. Changes were observed in the content of protein, fat, lactose, and carbohydrates, a slower fermentation process, changes in color, increased syneresis, and changes in texture depending on the proportion of oat beverage. The optimal proportions of the cow’s milk and oat beverage mixture, ensuring the desired sensory, textural, and microbiological stability, were found to be in the range of 25–50% oat beverage addition.